Perbedaan Pengetahuan antara Sebelum dan Sesudah Pelatihan Mengenai Pentingnya Antenatal Care pada Kader Posyandu Desa Gunungtiga, Kecamatan Ulubelu, Kabupaten Tanggamus, Lampung - Charisatus Sidqotie; Fitria Saftarina (MAJORITY, 2020)
In 2015, the maternal mortality rate (MMR) in Tanggamus Regency amounted to 16 events consisting of 3 maternal deaths, 4 maternal deaths, 9 postpartum maternal deaths. Efforts to accelerate the reduction of MMR can be done by ensuring that every mother is able to access quality maternal health services, one of which is health care for pregnant women (antenatal care/ANC). ANC must meet the minimum frequency of 4 visits. However, the uneven distribution of health workers and the low knowledge of health cadres about the importance of ANC is still low, so the number of ANC visits is still low. This study used the quassy experimental method with the design of one group pretest-posttest design. The sampling technique is total sampling. The research was conducted from April to July 2018, located in Gunungtiga Village, Ulubelu District, Tanggamus Regency, Lampung. The samples that were obtained were 18 Posyandu cadres. The median value of the knowledge pre-test is 30, while the median value of the post-test knowledge is 80. The results of the bivariate analysis p = 0,000. There was a significant difference between the training regarding the importance of antenatal care for the knowledge of Posyandu cadres in Gunungtiga Village.